Ocena technologii na wczesnym etapie ich rozwoju: wyzwanie badawcze i społeczne - Monika Małek-Orłowska (Studia Philosophica Wratislaviensia)
The author postulates and justifies the need for developing a research programme that would provide a starting point for the formulation of a universal model for the early-stage technology assessment. Referring to the moral status of innovation the author points to the necessity for interdisciplinary collaboration from the conceptual stage. The justification for this endeavour is provided by the demand for social control over technology, the ethical obligation to identify risks and the imperative of responsibility. Systematic philosophical reflection plays a significant role in the proposal presented, both as a link between disciplines and as a unifying meta-level.